Role of ethylene in responses of plants to nitrogen availability - Khan, M. I. R.; Trivellini, Alice; Fatma, Mehar; Masood, Asim; Francini, Alessandra; Iqbal, Noushina; Ferrante, Antonio; Khan, Nafees A. (Frontiers in Plant Science, 2015)
Ethylene is a plant hormone involved in several physiological processes and regulates the plant development during the whole life. Stressful conditions usually activate ethylene biosynthesis and signalling in plants. The availability of nutrients, shortage or excess, influences plant metabolism and ethylene plays an important role in plant adaptation under suboptimal conditions. Among the plant nutrients, the nitrogen (N) is one the most important mineral element required for plant growth and development. The availability of N significantly influences plant metabolism, including ethylene biology. The interaction between ethylene and N affects several physiological process such as leaf gas exchanges, roots architecture, leaf, fruits and flowers development. Low plant N use efficiency leads to N loss and N deprivation, which affect ethylene biosynthesis and tissues sensitivity, inducing cell damage and ultimately lysis. Plants may respond differently to N availability balancing ethylene production through its signalling network. This review discusses the recent advances in the interaction between N availability and ethylene at whole plant and different organ levels, and explores how N availability induces ethylene biology and plant responses. Exogenously applied ethylene seems to cope the stress conditions and improves plant physiological performance. This can be explained considering the expression of ethylene biosynthesis and signalling genes under different N availability. A greater understanding of the regulation of N by means of ethylene modulation may help to increase N use efficiency and directly influence crop productivity under conditions of limited N availability, leading to positive effects on the environment. Moreover, efforts should be focused on the effect of N deficiency or excess in fruit trees, where ethylene can have detrimental effects especially during postharvest.